(3GdJOGhj HGdWHjYI ef QCSc Edi CNeU bOejc (B:s [(3YdGLGJ HCSdhH GdeGcQhHjhJc ddMaGX Ydi UMJc(B] /s - (3EjgGQG, chQfjdjGs; (3GjgGQG, gjQeGf,s 1920-1998 ([(3GdQjGV(B] :s (3ecJHI LQjQ,s, 2005)
(3jJfGhd GdcJGH cjajI GdJOGhj HGdCYTGH GdWHjYjI(B.s
(3Odjd TGed ef GdCda Gdi GdjGA fMh YdGL GdeTcdGJ GdUMjI HGSJYeGd GdCWYeI GdcGedI , hGdeSJMVQGJ GdOhGFjI , hGdJOdjc (B.s
Keywords: (3GdYdGL GdfHGJjs; (3GdfHGJGJ GdWHjIs